2018
DOI: 10.1186/s40554-018-0066-8
|View full text |Cite|
|
Sign up to set email alerts
|

Developing a systemic functional approach to teach multimodal literacy

Abstract: This article argues for the importance of teaching multimodal literacy in schools so as to adequately equip students to navigate the multimodal communicative landscape. Developing multimodal literacy in students is about developing in them the ability to view multimodal texts critically and for them to represent their ideas through the production of effective multimodal texts. This article describes an instructional approach developed to teach multimodal texts and describes the trial of the approach in a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 17 publications
3
58
0
4
Order By: Relevance
“…Research on multimodal pedagogy revealed that the implementation of this pedagogy could help English language learners develop their language and multimodal literacy skills (Coccetta, 2018;Dzekoe, 2017;Ganapathy, 2015;Hafner, 2014;Kaminski, 2019;Kumagai, Kanoeda, & Nishimata, 2016;K. Lee, Ardeshiri, & Cummins, 2016;Lim, 2018;Millaray, Cárcamo, Heraldo, & Larenas, 2016;Mulatsih, 2016;Ruan, 2015;Souzandehfar, Saadat, & Sahragard, 2014;Yi & Choi, 2015). As one of the few empirical studies, Lee, Ardehshiri and Cummin (2016) investigated the implementation of multiliteracies pedagogy in a Computer-Assisted Multiliteracies Programme (CAMP) setting in an English communication course in a Korean public middle school during the summer session.…”
Section: Theme Two: Multimodal Pedagogy Improved English Language Andmentioning
confidence: 99%
“…Research on multimodal pedagogy revealed that the implementation of this pedagogy could help English language learners develop their language and multimodal literacy skills (Coccetta, 2018;Dzekoe, 2017;Ganapathy, 2015;Hafner, 2014;Kaminski, 2019;Kumagai, Kanoeda, & Nishimata, 2016;K. Lee, Ardeshiri, & Cummins, 2016;Lim, 2018;Millaray, Cárcamo, Heraldo, & Larenas, 2016;Mulatsih, 2016;Ruan, 2015;Souzandehfar, Saadat, & Sahragard, 2014;Yi & Choi, 2015). As one of the few empirical studies, Lee, Ardehshiri and Cummin (2016) investigated the implementation of multiliteracies pedagogy in a Computer-Assisted Multiliteracies Programme (CAMP) setting in an English communication course in a Korean public middle school during the summer session.…”
Section: Theme Two: Multimodal Pedagogy Improved English Language Andmentioning
confidence: 99%
“…This finding is related to Lim (2018) that by having adequate education for pre-service teachers at universities or some workshops for in-office teachers through ongoing lifelong learning and putting knowledge into the classroom, teachers update their concepts and technology tools to 66 improve their ability to choose, controlling, and assessing information technology in their EFL teaching. Besides, Valtonen, Kukkonen, Kontkanen, Mäkitalo-Siegl, & Sointu (2018) also agree that technology, pedagogy, and knowledge content for English teachers provide insight into the framework of the teaching and learning process.…”
Section: Resultsmentioning
confidence: 96%
“…Those who are specifically interested in this complete digital set are called web pages, blogs, wikis, podcasts, various types of videos, video games, infographics, posters, brochures (for some examples from the context of writing L2). Multimodal literacy is about understanding affordability, namely the potential and limitations, the resources for making different meanings, and how they work together to produce coherent and cohesive multimodal texts (Lim, 2018).…”
mentioning
confidence: 99%
“…COMO ENSINAR NUMA PEDAGOGIA DA LEITURA REALIZADA ON-LINE PARA APRENDER Na teoria dos multiletramentos, educar indivíduos com habilidades necessárias à cidadania do século XXI depende crucialmente da disponibilização de contextos de aprendizagem desenhados de acordo com um repertório de processos básicos de aprendizagem (NEW LONDON GROUP, 1996;COPE, 2012;JEWITT, 2008;LIM, 2018)).…”
Section: Conhecimentounclassified